Cooperation in the birth of the current international regime of the Law of the Sea. The role of Latin American coastal countries - Castello, Vanesa (REVISTA ELECTRONICA IBEROAMERICANA, 2022)
The Law of the Sea has gone through different stages until the enactment of the United Nations Convention on the Law of the Sea in 1982, which gave rise to a comprehensive regime for the oceans. In this sense, within the framework of changes in the international system in terms of the number and variety of relevant actors, the Latin American coastal countries were protagonists and contributed greatly in reaching an agreement that gave birth to such a regime. Background in the internal and regional framework of these countries, as well as the position and defense of their own interests in the negotiation within the III United Nations Conference on the Law of the Sea, would be fundamental to arrive at a set of principles, norms, and rules of procedure and decision making that would reflect the configuration of the international community. This article describes the cooperative actions carried out by the Latin American riparian countries prior to and during the negotiation process of the III Conference, for the birth of a new international regime relatively in line with their interests.